Specific Monovalent Cation Effects on Modification of Reovirus Infectivity by Chymotrypsin Digestion In Vitro - Borsa, J. (1973)
Specific monovalent cations control the modification of reovirus infectivity by chymotrypsin. Digestion in K(+), Rb(+), or Cs(+) reduces infectivity several logs, whereas in Na(+) or Li(+) digestion markedly enhances infectivity.